Geodetic Observations and Seismogenic Structures of the 2025 Mw 7.0 Dingri Earthquake: The Largest Normal Faulting Event in the Southern Tibet Rift - Qingyi Liu; Jun Hua; Yingfeng Zhang; Wenyu Gong; Jianfei Zang; Guohong Zhang; Hongyi Li (Remote Sensing)
The Mw 7.0 Dingri earthquake, which occurred on 7 January 2025, occurred at the southern end of the Xainza-Dinggyê Fault Zone within the South Tibet Rift (STR) system, in the Dengmecuo graben. It is the largest normal-faulting event in the region recorded by modern instruments. Using Sentinel-1A and Lutan SAR data combined with strong-motion records, we derived the coseismic surface deformation and slip distribution. InSAR interferograms and displacement vectors confirm a typical normal-faulting pattern. The slip model, based on an elastic half-space assumption, identifies the Dengmecuo Fault as the source fault, with an average strike of ~187° and a dip of ~55°. The rupture was concentrated within the upper 10 km, with a maximum slip of 4–5 m at ~5 km depth, extending to the surface with ~3 m vertical displacement. Partial rupture (≤2 m) in the southern segment (5–10 km depth) did not reach the surface, likely due to lacustrine deposits or possible post-seismic stress release. The rupture bottom intersects the fault plane of the South Tibet Detachment System (STDS), suggesting a restraining effect on coseismic rupture propagation. Considering stress transfer along the Main Himalayan Thrust (MHT), we propose that the 2025 Dingri earthquake is closely associated with stress transfer following the 2015 Gorkha earthquake in the lower Himalayas.